Prehistoric Copper Mining in Michigan : The Nineteenth-Century Discovery of "Ancient Diggings" in the Keweenaw Peninsula and Isle Royale - Halsey, John R. (Book collections on Project MUSE., 2018)
"Discusses how nineteenth-century explorers and miners discovered evidence of prehistoric copper mining in the Upper Peninsula of Michigan and how that discovery ultimately led to the destruction of the prehistoric archaeological sites they found"--